Numerical investigation of a compact and lightweight thermal management system with axially mounted cooling tubes for cylindrical lithium-ion battery module. (1st July 2023) - Shan, Shuai; Li, Li; Xu, Qiang; Ling, Lei; Xie, Yajun; Wang, Hongkang; Zheng, Keqing; Zhang, Lanchun; Bei, Shaoyi
Abstract: To construct a compact and lightweight cooling system for cylindrical batter module, developing cooling tubes inserted into spaces between batteries is a promising way. Yet, the constant distance kept between adjacent cells in battery array makes the reported weight ratio values not satisfactory enough. Merits and demerits between different battery arrangement modes (staggered and aligned) are also unclear. Therefore, in this work, a novel liquid cooling thermal management system with axially mounted cooling tubes inserted into spaces between tightly assembled batteries is presented to provide a compact and lightweight solution to the cooling of cylindrical battery module. Designs with staggered and aligned battery arrangements are compared. Corresponding results show that design with staggered battery arrangement is superior to the aligned one based on the trade-off of different design requirements including cooling performance, system weight and volume cost. BTMS with staggered design reports a remarkably high performance in terms of the lightweight extent, which only accounts for 5.4 wt% of the battery module, much lower than those in previous studies. Further, extended studies are performed for the optimization of BTMS with staggered battery arrangement and the results could provide useful guidance in the future design of BTMS for cylindrical battery modules. Highlights: BTMS with cooling tubes inserted in spaces between tightly assembled batteries is studied. Designs with staggered and aligned battery arrangements are compared. A remarkable weight ratio (5.4 wt%) of BTMS in the battery module is reported.